Merkel cell carcinoma Pathological and molecular aspects of diagnosis and clinical features - Majewska, Hanna; Biernat, Wojciech (Polish Journal of Pathology, 2010)
Merkel cell carcinoma (MCC) is an aggressive neoplasm of the skin usually developing in the elderly. The morphological and phenotypical characteristics of Merkel cell carcinoma was recently expanded by the molecular profile. The current review is a compilation of these data, which may enable better understanding of the histogenesis and potential target therapy in this rare tumour of the skin.